Analisis Faktor Pemberian Imunisasi Rubella di Kelurahan Wakangka Kabupaten Buton - Andriani, Rinita; Wahyuddin, Wahyuddin; Darmawan, Agus (Jurnal Kebidanan Malakbi, 2020)
Rubella disease is a contagious disease that can be prevented by immunization. This disease is characterized by the appearance of a rash and mild fever or similar to other viral diseases such as measles and scarlet fever. Rubella is more common in adults than in children. In adults, 70% of cases of rubella disease cause arthritis or atrophy and joint pain. This study aims to determine the relationship of knowledge, attitudes and religion in the administration of rubella immunization in Wakangka Village, Kapontori District. This type of research is quantitative analytic observational approach is a study that explains the relationship between variables through hypothesis testing. The number of samples was 72 people. Samples were taken using simple random sampling technique. Data analysis using univariate and bivariate analysis using chi square test is to see the relationship between variables. The results showed knowledge with a value of p = 0,000 (α <0.05), maternal attitudes with a value of p = 0,000 (α <0.05), and religion with a value of p = 0.995 (α> 0.05). The conclusion in this study is that there is a relationship between knowledge and attitudes with the provision of Rubella Immunization, but there is no relationship between religion and Rubella immunization. It is recommended that people who have children aged 5 months to 15 years be rubella immunized to avoid being recorded.